Hyperandrogenism due to ovarian tumour mimicking PCOS: a case report - Pidaparthy, Padmaja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Hyperandrogenism is the most common endocrine disorder in reproductive age group. While 82% of the cases are due to PCOS, steroid cell tumours account for less than 1% of cases. These tumours are mostly seen in perimenopausal women and 25-30% of these tumours show malignant potential. Hysterectomy with bilateral salpingo-oophorectomy is the recommended treatment. In a young patient unilateral salpingo-oophorectomy and subsequent follow up can be offered. We present one such rare case of a young patient coming with menstrual irregularities, virilising symptoms and infertility, all features mimicking PCOS. She was diagnosed with a steroid cell tumour and successfully treated.